Periodical Technical Inspection on Taxi Roadworthiness - Zulkipli, Z.H.; Sarani, R.; Zainal Abidin, A.N.S.; Solah, M.S.; Osman, M.R. (Journal of the Society of Automotive Engineers Malaysia, 2021)
The objectives of this study are to analyse the taxi roadworthiness resulting from the mandatory Periodic Technical Inspection (PTI). The data was obtained from a local vehicle inspection company, PUSPAKOM and the dataset only involved taxis which had been sent to PUSPAKOM for roadworthiness inspection which includes initial inspection and periodic inspection. Majority of the taxis are EA type (Perkhidmatan Awam Teksi) with about 60% of the overall of the taxi population. Using logistic regression analysis, the probability of failure of PTI by the taxi was developed. The results indicate that with the existing periodic technical inspection for roadworthiness, the probability of an EA type taxi to have failed the periodic inspection (PTI) reaches 50% after Year-2. Moreover, for a well-maintained EA type taxi that had never failed before, the probability of it to fail in the coming inspection would reach 50% in Year-5.